O4 Amino acid substitution in genotype 3a hepatitis C virus polymerase protein affects responses to sofosbuvir and interferon alpha and inhibits apoptosis. (28th September 2020) - Lee, Wing-yiu Jason; Jones, Meleri; Wing, Peter AC; Rajagopal, Swathi; Foster, Graham R
Abstract : Introduction: We have previously shown, by both genetic and functional analyses that a substitution in HCV G3 NS5b at amino acid 150 (alanine [A] to valine [V]), V at position 150 resulted in a reduced response to sofosbuvir, (Wing et al Gastroenterology 2019). Since response to sofosbuvir containing regimens in patients with G3 HCV is reduced in those previously treated unsuccessfully with interferon we hypothesize that this substitution might affect the response to interferon. Results: Using sub-genomic replicons we find that the presence of the A150V substitution reduces the response to IFN alpha (figure 1 . IC50 of S52_WT=1.162IU/ml and IC50 of S52_A150V=14.45IU/ml, 12.4-fold difference). Induction of interferon-stimulated genes in A150V replicon cells was unaffected in cells expressing A150V replicons but activation of PKR was reduced. Blockade of PKR activity reduced the effect of IFN on wildtype replicon, whereas augmented PKR activation promoted IFN antiviral effects in A150V replicons. Hence the A150V substitution inhibits IFN antiviral effects by inhibiting PKR. Since interferon and PKR play important roles in apoptosis we examined the effect of A150V replicons on apoptosis – these replicons reduced apoptosis (% increase of cell death by IFN cf. untreated in WT were 11% in wild-type and 3% in A150V). Conclusion: Polymorphisms reducing response rates to DAAs may alter both antiviral and cellular responses that may have implications on malignant transformation.